The Effect Of Mindfulness Training On Reducing Anxiety In Arabic Speaking Among Students At MTs Wahid Hasyim 1 Dau Malang - Muzamil R Pawi; Abidin, Munirul; Penny Respati Yurisa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Speaking anxiety is a psychological factor that frequently inhibits students’ confidence and fluency in Arabic language learning. One approach with potential to address this issue is Mindfulness Training, which emphasizes non-judgmental awareness of thoughts, emotions, and bodily responses. This study aimed to analyze the effect of Mindfulness Training in reducing Arabic speaking anxiety in terms of physiological, cognitive, and affective aspects, as well as to identify the aspect most influenced by the intervention. A quantitative approach was employed using a pre-experimental one-group pretest–posttest design. The participants consisted of 58 eighth-grade students at MTs Wahid Hasyim 1 Dau, Malang. Data were collected through an Arabic speaking anxiety questionnaire administered before and after six intervention sessions, and analyzed using paired sample t-tests and the Friedman test. The results revealed a significant reduction in speaking anxiety across all aspects, with a significance value of p = 0.000. The cognitive aspect showed the greatest decrease (Δ = 9.97), followed by the physiological (Δ = 8.48) and affective aspects (Δ = 7.26). These findings confirm that Mindfulness Training is effective in reducing Arabic speaking anxiety, particularly through changes in students’ cognitive processes.